2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333528
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of an algorithm for the identification of time-varying joint stiffness

Abstract: Previously, we described a time-varying, parallel-cascade system identification algorithm that estimates intrinsic and reflex stiffness dynamics. It uses an iterative technique, in conjunction with established, time-varying, identification methods, to estimate the two pathways from ensembles of input and output realizations having the same time-varying behavior. This paper presents the results of a study that systematically evaluated the performance of the algorithm. Simulations were used to determine the algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…Other studies have used ensemble-based method to evaluate the effect of activation level on joint stiffness. Visser ( 2010 ) studied ankle joint stiffness during a sinusoidal torque matching task, where a monotonic increase in elastic parameter with voluntary torque was observed similar to the observation of this study. The main difference with our results was that Visser ( 2010 ) found two peaks in the reflex gain at the lowest and highest activation levels.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Other studies have used ensemble-based method to evaluate the effect of activation level on joint stiffness. Visser ( 2010 ) studied ankle joint stiffness during a sinusoidal torque matching task, where a monotonic increase in elastic parameter with voluntary torque was observed similar to the observation of this study. The main difference with our results was that Visser ( 2010 ) found two peaks in the reflex gain at the lowest and highest activation levels.…”
Section: Discussionsupporting
confidence: 75%
“…Visser ( 2010 ) studied ankle joint stiffness during a sinusoidal torque matching task, where a monotonic increase in elastic parameter with voluntary torque was observed similar to the observation of this study. The main difference with our results was that Visser ( 2010 ) found two peaks in the reflex gain at the lowest and highest activation levels. Also, Ludvig and Perreault ( 2014 ) used a similar ensemble-based method to study knee stiffness during rapid activation and reported similar results for the elastic parameter.…”
Section: Discussionsupporting
confidence: 75%